HAVE THE BOYS GONE OVERBOARD? A STUDY TO INVESTIGATE THE ACADEMIC PLIGHT OF PRIMARY SCHOOL BOYS - Mather, Nazarana (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Assessments conducted nationally and internationally have suggested that boys are achieving lower results than their female counterparts in all subjects in school. Historically, boys have performed better than girls academically. However, current research internationally into this situation has indicated that girls are outperforming boys in all subjects [see: Philippines (Fontanos and Ukampo, 2019); South Africa (Mather, 2019); Finland (Lahelma, 2021); Kenya (Muyaka & Malena); Pakistan (Ullah & Ullah, 2021); and Spain: (Sainz, Sole & Fabregues, 2021). Sainz, Sole & Fabregues (2021) state that in countries like Spain, boys are more likely to fail in school than girls, and during the last decade boys show a higher disposition to drop out of school earlier than girls. For instance, in 2019, 21.4% of the learners who dropped out were boys and 13% were girls (MEFP, 2020). In South Africa learners in Grades 3, 6 and 9 wrote the Annual National Assessments (ANA) in Home Language and Maths. The results found that girls performed better than boys in both subjects in all provinces and in all participating grades (DBE, 2013; DBE, 2014). This study sought to investigate the academic crisis of boys and foreground the gender gap in academic performance and was carried out as a desk study. Desk research or secondary research is a research method that involves using already existing data by conducting research through web searches, online platforms, industry reports, or even physical books (Gell, 2020). In this study rigorous research has been conducted using online platforms such as Ebscohost and Sabinet to source relevant, credible, and current research related to phenomenon that is being investigated. It was found that a gender gap in academic performance exists both nationally and internationally, and in all grades and subjects. It was concluded that some research has been conducted into this gender gap. However more research about causes of this underperformance and context-specific strategies that can be implemented to help bridge this gap, especially since the Covid19 lockdown, is needed to help bring the boys back on board.